От составителей [Lazar Fleishman at 80: Section Editors’ Note] - Poljakov, Fedor; Utgof, Grigori (Slavica Revalensia, 2026)
This brief note precedes the anniversary section, which contains 13 articles written by 14 scholars on the occasion of the 80th birthday of Prof. Lazar Fleishman of Stanford University (and Dr. honoris causa of Tallinn University). The section’s contributors are: Alexander Ospovat (Moscow / Los Angeles), Alexander Dolinin (Madison), Roman Timenchik (Jerusalem), Irina Belobrovtseva (Tallinn), Alexander Lavrov (Saint Petersburg), Fedor Poljakov (Vienna), David M. Bethea (Madison), Andrei Ustinov (San Francisco), Vladimir Khazan (Jerusalem), Boris Ravdin (Riga) and Benjamin Musachio (Princeton / Riga), Michael Wachtel (Princeton), Konstantin Azadovskii (Saint Petersburg), and Stefano Garzonio (Pisa / Florence).